2017
DOI: 10.1186/s40327-017-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

A semi-automated approach to generate 4D/5D BIM models for evaluating different offshore oil and gas platform decommissioning options

Abstract: Background: Offshore oil and gas platforms generally have a lifetime of 30 to 40 years, and platform decommissioning is a major issue because many of the existing offshore oil and gas platforms are reaching the end of their service life. There are many possible options for decommissioning offshore oil and gas platforms, and each decommissioning option can be implemented using different methods and technologies. Therefore, it is necessary to have a clear understanding and in-depth evaluation of each decommissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The use of 3D, 4D, and 5D BIM in construction today is extremely beneficial to consultants/contractors in terms of reducing claims to service providers. Previous research by the researchers have revealed relevant findings (Noviani et al, 2022;J. C. P. Cheng et al, 2017).…”
Section: Introductionmentioning
confidence: 91%
“…The use of 3D, 4D, and 5D BIM in construction today is extremely beneficial to consultants/contractors in terms of reducing claims to service providers. Previous research by the researchers have revealed relevant findings (Noviani et al, 2022;J. C. P. Cheng et al, 2017).…”
Section: Introductionmentioning
confidence: 91%
“…For that, a coding system is required (Gledson and Greenwood, 2016). The connection between BIM and planning can be automated using the following methods: create a consistent coding system between activities and BIM elements: consists of creating code-based matching rules, 3D model elements and planning activities are generally coded with a Common Unique Identifier (Cheng et al , 2017); and create a consistent language system between activities and BIM elements: consists of creating language-based matching rules that match 3D model elements to activities by their names (Cheng et al , 2017). …”
Section: Advances In Automated Generation Of Four-dimensional Buildin...mentioning
confidence: 99%
“…create a consistent coding system between activities and BIM elements: consists of creating code-based matching rules, 3D model elements and planning activities are generally coded with a Common Unique Identifier (Cheng et al , 2017); and…”
Section: Advances In Automated Generation Of Four-dimensional Buildin...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of increasing energy demand, the offshore oil and gas industry is using the advanced technologies to explore more remote, deeper, and harsh environments [1][2][3][4][5][6]. Thus, hazard for accidental loads and the related engineering problems are increasing and both the risk management for such an issue and technical design method for getting a resistance against the potential incidents are becoming more challenging [7].…”
Section: Introductionmentioning
confidence: 99%